A numerical study of erosion void and corrosion effects on the performance of buried corrugated steel culverts. (1st June 2022) - Nakhostin, E.; Kenny, S.; Sivathayalan, S.
Highlights: The loss of surface contact between culvert and soil is the key parameter that affects culvert performance and integrity. Location of void adjacent to the culvert changes the surface load distribution in the backfill with high pressure (soil-culvert interaction) Intact culverts approach yield stress when backfill is deteriorated by erosion void located in the upper half of the culvert/soil section. The culvert is approaching the yield stress for cases deteriorated by combined erosion void and corrosion and thrust is the influential internal force. Abstract: The mechanical response of a buried corrugated steel culvert, that is deteriorated due to corrosion and/or soil erosion, subject to surface loading and overburden is simulated using continuum finite element methods. The three-dimensional numerical modelling procedures were verified for culvert diameter changes using third party full-scale experimental data. The numerical simulations evaluated the mechanical response in terms of displacement, section force and moment, and equivalent plastic strain relative to the intact culvert/soil system across a range of design parameters. The sensitivity study evaluated the soil and culvert damage state as defined by the location and volume of soil erosion voids adjacent to the culvert perimeter and corrosion at invert with different angles. The mechanical response of the culvert exhibited greater sensitivity for soil erosion voids located at or above the springline with the higher potential for failure and decreased service life. The impact on the mechanical response was localized for soil erosion voids below the springline, and the culvert material can approach yield if void creation is combined with corrosion deterioration.